SPIRITUAL MENTAL GUIDANCE WITH ISLAMIC PSYCHOTHERAPY FOR CLIENTS OF SOCIAL REHABILITATION CENTER - Nur Azizah; Alief Budiyono; Nela Amalia; Adhitya Ridwan Budhi Prasetyo Nugroho (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
Drug abuse can cause dependence and many effects, among which the impact can occur on the mental and spiritual. Mental and spiritual damage can influence drug abuse. Rehabilitation is one solution to cure drug abuse. This research aims to find Islamic Psychotherapy-Based Spiritual Mental Guidance for Clients of the Social Rehabilitation Center for Drug Abuse Victims Satria in Baturraden. This research is carried out by providing insight and knowledge to students of the Islamic Guidance and Counseling study program regarding the implementation of Islamic Psychotherapy-Based Spiritual Mental Guidance for Clients of the Social Rehabilitation Center for Drug Abuse Victims Satria